Wear-resistant and puncture-resistant gloves and processing technology thereof
By thermal twisting and heat setting treatment of ultra-high molecular weight polyethylene fibers, combined with impregnation liquid and wear-resistant coating, the problems of insufficient puncture and wear resistance of traditional gloves are solved, achieving more efficient protection and longer service life.
Patent Information
- Application Number
- CN202310587257.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-05-24
AI Technical Summary
Traditional protective gloves cannot provide sufficient protection in special occupations, especially in terms of puncture and wear resistance, resulting in vulnerability to damage and scrapping of gloves.
Ultra-high molecular weight polyethylene fibers are used for heat twisting and heat setting to prepare puncture-resistant fabrics, and the puncture-resistant and wear-resistant properties of the fabrics are enhanced by a combination of impregnation liquid and wear-resistant coatings.
It significantly improves the puncture and wear resistance of gloves, extends the service life of gloves, and provides a higher level of protection.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gloves, in particular to a pair of wear-resistant and puncture-resistant gloves and a processing technology thereof. Background Art
[0002] For some practitioners of special occupations, they often need to wear gloves with special functions as protection at work. For example, when medical staff use them for medical treatment, their fingers are easily pierced by needles or other sharp objects, which may lead to infection with AIDS or other viruses and bacteria. Therefore, they need to wear protective gloves. In the fields of cable, glass, wood manufacturing machinery manufacturing, etc., workers need to wear special protective gloves in their daily work to protect their hands. For the working groups in these special industries, they often encounter situations of being stabbed by sharp objects, and traditional protective gloves with single functions can no longer provide sufficient protection for practitioners. In addition, due to the needs of work, the crowns of the thumb, index finger and middle finger of the gloves are very easy to wear and break during work, and the fingertips may fall off and crack, which will lead to the overall scrapping of the gloves.
[0003] In order to overcome the defects of the prior art, the present invention provides a wear-resistant and puncture-resistant glove and a processing technology thereof. Summary of the invention
[0004] The object of the present invention is to provide a wear-resistant and puncture-resistant glove and a processing technology thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A processing technology for wear-resistant and puncture-resistant gloves comprises the following steps:
[0007] Step 1: heat-twisting and heat-setting the yarn of ultra-high molecular weight polyethylene fiber to prepare a fabric;
[0008] Step 2: dilute the impregnation liquid and anhydrous ethanol, then immerse the fabric in the dilution, and obtain the puncture-resistant fabric after drying;
[0009] Step three: Mix epoxy resin, aluminum hydroxide, titanium boride and curing agent, and stir them ultrasonically to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric, and obtain the finished product after drying and cutting.
[0010] More optimally, in step 1, heat twisting is performed at 70-80°C to twist the yarn, and heat setting is performed at 55-65°C for 0.5-1.5h.
[0011] More optimally, in step 2, the preparation steps of the impregnation solution are:
[0012] S1: Mix transition metal nitrate, pyridine-2,6-dicarboxylic acid and deionized water, and stir ultrasonically for 40-60 minutes. Then, hydrothermally react the reactants at 100-120°C for 65-75 hours. After cooling to 20-25°C, vacuum filter, wash and dry to obtain MOF material.
[0013] S2: dissolving polylactic acid in polyethylene glycol, then adding MOF material to form a mixture, ball-milling the mixture for 10-14 hours to obtain a suspension; adding Ca(NO3)2·4H2O to the suspension, and ball-milling again for 10-14 hours to obtain an impregnation solution.
[0014] More optimally, in the preparation of the impregnation solution, by mass, 8-10 parts of transition metal nitrate, 8-10 parts of pyridine-2,6-dicarboxylic acid, 24-30 parts of deionized water, 6-12 parts of polylactic acid, 40-50 parts of polyethylene glycol, 6-12 parts of MOF material obtained in S1, and 15-25 parts of Ca(NO3)2·4H2O.
[0015] More optimally, in step 2, the impregnation liquid and anhydrous ethanol are diluted in a volume ratio of 1:1 to a mass concentration of 15-25%, the fabric is impregnated for 2-4 minutes, and dried at 60-70°C for 4-6 hours.
[0016] More optimally, in step three, in the preparation of the wear-resistant coating, by mass, 25-35 parts of epoxy resin, 3-5 parts of aluminum hydroxide, 3-5 parts of titanium boride, and 10-20 parts of curing agent are used.
[0017] More optimally, in step three, the curing agent is a cardanol-modified amine curing agent.
[0018] More optimally, in step three, the ultrasonic stirring is carried out at a rotation speed of 1500-2000 rpm and a temperature of 40-50° C. for 60-80 min.
[0019] More optimally, in step 3, the coating amount is 30-40g / m 2 , dry at 75-85℃ for 4-6h.
[0020] Beneficial effects of the present invention:
[0021] The invention significantly increases the tightness and linear density of the yarn by performing heat twisting and heat setting treatment on the fabric, thereby improving the fabric density and enhancing the mechanical strength of the yarn. In addition, the invention also prepares a wear-resistant coating and coats it on the surface of the fabric to enhance the surface wear resistance of the fabric.
[0022] The present invention is characterized in that an impregnation liquid is prepared. The principle of the impregnation liquid is as follows: a carboxyl-rich MOF material is prepared using transition metal nitrate and pyridine-2,6-dicarboxylic acid as raw materials; then the MOF material is used as raw material, and carboxyl-rich polylactic acid, polyethylene glycol dispersant, and Ca(NO3)2·4H2O are added to carry out a mixed reaction to prepare an impregnation liquid. The impregnation liquid prepared by the present invention has a very strong anti-puncture effect. On the one hand, it relies on the hydrogen bonding between the particles and the dispersion medium to form a spatial network structure to withstand the puncture of sharp objects; on the other hand, the present invention adds carboxyl-rich MOF material, polylactic acid and Ca(NO3)2·4H2O to form a spatial network structure. 2+ By fully pairing them, they can also form a huge network structure to withstand the puncture of sharp objects and have a good anti-puncture effect. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Source of raw materials:
[0025] Ultra-high molecular weight polyethylene fiber, provided by Jiangsu Putek New Material Technology Co., Ltd., model: PTC-10; epoxy resin, provided by Langfang Rongguang Energy Saving Technology Co., Ltd., model: E-44; cardanol modified amine curing agent, provided by Zhenli Shi strong supplier company, model: Gaskamine328; polyethylene glycol, provided by Guangzhou Chenyi New Materials Co., Ltd., model: CY-040; polylactic acid, provided by Shanghai Jiexun Plastic Co., Ltd., model: LX175; transition metal nitrate, provided by Shandong Liang New Material Technology Co., Ltd., model: LA231045.
[0026] Example 1: Step 1: twisting the yarn of ultra-high molecular weight polyethylene fiber at 80° C., and then heat-setting it at 65° C. for 1.5 h to prepare a fabric;
[0027] Step 2: Preparation of impregnation solution:
[0028] S1: 10 parts of transition metal nitrate, 10 parts of pyridine-2,6-dicarboxylic acid and 30 parts of deionized water were mixed, ultrasonically stirred for 60 minutes, and then the reactants were hydrothermally reacted at 120°C for 75 hours. After cooling to 25°C, vacuum filtration, washing and drying were performed to obtain MOF material;
[0029] S2: 12 parts of polylactic acid were dissolved in 50 parts of polyethylene glycol, and then 12 parts of MOF material were added to form a mixture, and the mixture was ball-milled for 14 hours to obtain a suspension; 25 parts of Ca(NO3)2·4H2O were added to the suspension, and the mixture was ball-milled again for 14 hours to obtain an impregnation solution;
[0030] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 4 minutes, and dry at 70°C for 6 hours to obtain the puncture-resistant fabric;
[0031] Step 4: Mix 25 parts of epoxy resin, 3 parts of aluminum hydroxide, 3 parts of titanium boride and 10 parts of cardanol modified amine curing agent, stir at a speed of 2000 rpm and a temperature of 50°C for 80 minutes to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric, with a coating amount of 40g / m 2 ; Then dry it at 85℃ for 6h and cut it to get the finished product.
[0032] Example 2: Step 1: twisting the yarn of ultra-high molecular weight polyethylene fiber at 80° C., and then heat-setting it at 63° C. for 80 minutes to prepare a fabric;
[0033] Step 2: Preparation of impregnation solution:
[0034] S1: 10 parts of transition metal nitrate, 10 parts of pyridine-2,6-dicarboxylic acid and 30 parts of deionized water were mixed, ultrasonically stirred for 60 minutes, and then the reactants were hydrothermally reacted at 115°C for 73 hours. After cooling to 23°C, vacuum filtration, washing and drying were performed to obtain MOF material;
[0035] S2: 12 parts of polylactic acid were dissolved in 50 parts of polyethylene glycol, and then 12 parts of MOF material were added to form a mixture, and the mixture was ball-milled for 14 hours to obtain a suspension; 25 parts of Ca(NO3)2·4H2O were added to the suspension, and the mixture was ball-milled again for 13 hours to obtain an impregnation solution;
[0036] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 4 minutes, and dry at 68°C for 5.5 hours to obtain the puncture-resistant fabric;
[0037] Step 4: Mix 25 parts of epoxy resin, 3 parts of aluminum hydroxide, 3 parts of titanium boride and 10 parts of cardanol modified amine curing agent, stir for 75 minutes at a speed of 1875 rpm and a temperature of 47°C to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric at a coating amount of 40 g / m 2 ; Then dry at 83℃ for 5.5h and cut to obtain the finished product.
[0038] Example 3: Step 1: twisting the yarn of ultra-high molecular weight polyethylene fiber at 75° C., and then heat-setting it at 60° C. for 60 minutes to prepare a fabric;
[0039] Step 2: Preparation of impregnation solution:
[0040] S1: 10 parts of transition metal nitrate, 10 parts of pyridine-2,6-dicarboxylic acid and 30 parts of deionized water were mixed, ultrasonically stirred for 50 minutes, and then the reactants were hydrothermally reacted at 110°C for 70 hours. After cooling to 22°C, vacuum filtration, washing and drying were performed to obtain MOF material;
[0041] S2: 12 parts of polylactic acid were dissolved in 50 parts of polyethylene glycol, and then 12 parts of MOF material were added to form a mixture, and the mixture was ball-milled for 12 hours to obtain a suspension; 25 parts of Ca(NO3)2·4H2O were added to the suspension, and the mixture was ball-milled for 12 hours again to obtain an impregnation solution;
[0042] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 3 minutes, and dry at 65°C for 5 hours to obtain the puncture-resistant fabric;
[0043] Step 4: Mix 25 parts of epoxy resin, 3 parts of aluminum hydroxide, 3 parts of titanium boride and 10 parts of cardanol modified amine curing agent, stir for 70 minutes at a speed of 1750 rpm and a temperature of 45°C to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric at a coating amount of 40 g / m 2 ; Then dry it at 80℃ for 5h and cut it to get the finished product.
[0044] Example 4: Step 1: twisting the yarn of ultra-high molecular weight polyethylene fiber at 73° C., and then heat-setting it at 57° C. for 45 minutes to prepare a fabric;
[0045] Step 2: Preparation of impregnation solution:
[0046] S1: 10 parts of transition metal nitrate, 10 parts of pyridine-2,6-dicarboxylic acid and 30 parts of deionized water were mixed, ultrasonically stirred for 45 minutes, and then the reactants were hydrothermally reacted at 105°C for 68 hours. After cooling to 21°C, vacuum filtration, washing and drying were performed to obtain MOF material;
[0047] S2: 12 parts of polylactic acid were dissolved in 50 parts of polyethylene glycol, and then 12 parts of MOF material were added to form a mixture, and the mixture was ball-milled for 12 hours to obtain a suspension; 25 parts of Ca(NO3)2·4H2O were added to the suspension, and the mixture was ball-milled again for 11 hours to obtain an impregnation solution;
[0048] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 3 minutes, and dry at 63°C for 4.5 hours to obtain the puncture-resistant fabric;
[0049] Step 4: Mix 25 parts of epoxy resin, 3 parts of aluminum hydroxide, 3 parts of titanium boride and 10 parts of cardanol modified amine curing agent, stir for 65 minutes at a speed of 1625 rpm and a temperature of 43°C to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric at a coating amount of 40 g / m 2 ; Then dry it at 78℃ for 4.5h and cut it to get the finished product.
[0050] Example 5: Step 1: twisting the yarn of ultra-high molecular weight polyethylene fiber at 73° C., and then heat-setting it at 56° C. for 35 minutes to prepare a fabric;
[0051] Step 2: Preparation of impregnation solution:
[0052] S1: 10 parts of transition metal nitrate, 10 parts of pyridine-2,6-dicarboxylic acid and 30 parts of deionized water were mixed, ultrasonically stirred for 45 minutes, and then the reactants were hydrothermally reacted at 102°C for 67 hours. After cooling to 21°C, vacuum filtration, washing and drying were performed to obtain MOF material;
[0053] S2: 12 parts of polylactic acid were dissolved in 50 parts of polyethylene glycol, and then 12 parts of MOF material were added to form a mixture, and the mixture was ball-milled for 11 hours to obtain a suspension; 25 parts of Ca(NO3)2·4H2O were added to the suspension, and the mixture was ball-milled again for 10.5 hours to obtain an impregnation solution;
[0054] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 3 minutes, and dry at 63°C for 4.5 hours to obtain the puncture-resistant fabric;
[0055] Step 4: Mix 25 parts of epoxy resin, 3 parts of aluminum hydroxide, 3 parts of titanium boride and 10 parts of cardanol modified amine curing agent, stir for 63 minutes at a speed of 1550 rpm and a temperature of 42°C to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric at a coating amount of 40 g / m 2 ; Then dry at 76℃ for 4.5h and cut to obtain the finished product.
[0056] Example 6: Step 1: twisting the yarn of ultra-high molecular weight polyethylene fiber at 70° C., and then heat-setting it at 55° C. for 30 minutes to prepare a fabric;
[0057] Step 2: Preparation of impregnation solution:
[0058] S1: 10 parts of transition metal nitrate, 10 parts of pyridine-2,6-dicarboxylic acid and 30 parts of deionized water were mixed, ultrasonically stirred for 40 minutes, and then the reactants were hydrothermally reacted at 100°C for 65 hours. After cooling to 20°C, vacuum filtration, washing and drying were performed to obtain MOF material;
[0059] S2: 12 parts of polylactic acid were dissolved in 50 parts of polyethylene glycol, and then 12 parts of MOF material were added to form a mixture, and the mixture was ball-milled for 10 hours to obtain a suspension; 25 parts of Ca(NO3)2·4H2O were added to the suspension, and the mixture was ball-milled again for 10 hours to obtain an impregnation solution;
[0060] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 2 minutes, and dry at 60°C for 4 hours to obtain the puncture-resistant fabric;
[0061] Step 4: Mix 25 parts of epoxy resin, 3 parts of aluminum hydroxide, 3 parts of titanium boride and 10 parts of cardanol modified amine curing agent, stir for 60 minutes at a speed of 1500 rpm and a temperature of 40°C to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric at a coating amount of 40 g / m 2 ; Then dry it at 75℃ for 4h and cut it to get the finished product.
[0062] Comparative Example 1: In step 2: preparation of the impregnation solution, the amount of MOF material is halved, and the rest is the same as in Example 1, and the specific steps are as follows: Step 1: The yarn of ultra-high molecular weight polyethylene fiber is twisted at 80°C, and then heat-set at 65°C for 1.5h to prepare a fabric;
[0063] Step 2: Preparation of impregnation solution:
[0064] S1: 10 parts of transition metal nitrate, 10 parts of pyridine-2,6-dicarboxylic acid and 30 parts of deionized water were mixed, ultrasonically stirred for 60 minutes, and then the reactants were hydrothermally reacted at 120°C for 75 hours. After cooling to 25°C, vacuum filtration, washing and drying were performed to obtain MOF material;
[0065] S2: 12 parts of polylactic acid were dissolved in 50 parts of polyethylene glycol, and then 6 parts of MOF material were added to form a mixture, and the mixture was ball-milled for 14 hours to obtain a suspension; 25 parts of Ca(NO3)2·4H2O were added to the suspension, and the mixture was ball-milled again for 14 hours to obtain an impregnation solution;
[0066] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 4 minutes, and dry at 70°C for 6 hours to obtain the puncture-resistant fabric;
[0067] Step 4: Mix 25 parts of epoxy resin, 3 parts of aluminum hydroxide, 3 parts of titanium boride and 10 parts of cardanol modified amine curing agent, stir at a speed of 2000 rpm and a temperature of 50°C for 80 minutes to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric, with a coating amount of 40g / m 2 ; Then dry it at 85℃ for 6h and cut it to get the finished product.
[0068] Comparative Example 2: In step 2: preparation of the impregnation solution, the MOF material is removed, and the rest is the same as in Example 1, and the specific steps are as follows: Step 1: The yarn of the ultra-high molecular weight polyethylene fiber is twisted at 80°C, and then heat-set at 65°C for 1.5h to prepare a fabric;
[0069] Step 2: dissolving 12 parts of polylactic acid in 50 parts of polyethylene glycol, ball milling for 14 hours to obtain a suspension; adding 25 parts of Ca(NO3)2·4H2O to the suspension, ball milling again for 14 hours to obtain an impregnation solution;
[0070] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 4 minutes, and dry at 70°C for 6 hours to obtain the puncture-resistant fabric;
[0071] Step 4: Mix 25 parts of epoxy resin, 3 parts of aluminum hydroxide, 3 parts of titanium boride and 10 parts of cardanol modified amine curing agent, stir at a speed of 2000 rpm and a temperature of 50°C for 80 minutes to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric, with a coating amount of 40g / m 2 ; Then dry it at 85℃ for 6h and cut it to get the finished product.
[0072] Comparative Example 3: omitting step 4, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: twisting the yarn of ultra-high molecular weight polyethylene fiber at 80° C., and then heat-setting the yarn at 65° C. for 1.5 h to prepare a fabric;
[0073] Step 2: Preparation of impregnation solution:
[0074] S1: 10 parts of transition metal nitrate, 10 parts of pyridine-2,6-dicarboxylic acid and 30 parts of deionized water were mixed, ultrasonically stirred for 60 minutes, and then the reactants were hydrothermally reacted at 120°C for 75 hours. After cooling to 25°C, vacuum filtration, washing and drying were performed to obtain MOF material;
[0075] S2: 12 parts of polylactic acid were dissolved in 50 parts of polyethylene glycol, and then 12 parts of MOF material were added to form a mixture, and the mixture was ball-milled for 14 hours to obtain a suspension; 25 parts of Ca(NO3)2·4H2O were added to the suspension, and the mixture was ball-milled again for 14 hours to obtain an impregnation solution;
[0076] Step 3: dilute the impregnation liquid and anhydrous ethanol in a volume ratio of 1:1 to a mass concentration of 25%, then immerse the fabric in the dilution for 4 minutes, dry it at 70°C for 6 hours to obtain the puncture-resistant fabric, and then cut it to obtain the finished product.
[0077] Detection test:
[0078] Stab-proof performance test: The test is carried out in accordance with GA68-2019 "Police Stab-proof Clothing". The size of the stab-proof material sample is 200mm×200mm. The tool is set to penetrate at a uniform speed of 5mm / min. The stab-proof performance experimental equipment and procedures are carried out in accordance with the provisions of Appendix A. The quasi-static puncture force of the test sample is tested.
[0079] Abrasion resistance test: According to the standard GB / T 21196.3-2007 "Test of abrasion resistance of textiles by Martindale method", the sample was cut into a diameter of 38±0.5mm and installed in the test instrument. 600 mesh water sandpaper was used as abrasive to test the number of abrasion resistance of the sample. The results are as follows:
[0080] Quasi-static puncture force / N Wear times / times Example 1 1850 9500 Example 2 1848 9498 Example 3 1847 9496 Example 4 1846 9495 Example 5 1844 9494 Example 6 1843 9493 Comparative Example 1 1757 9463 Comparative Example 2 1660 9433 Comparative Example 3 1848 8450
[0081] Conclusion: The dosage of Examples 1 to 6 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that the various properties of the fabric do not fluctuate significantly. Comparative Example 1: In step 2: preparation of the impregnation liquid, the dosage of MOF material is halved, and the rest is the same as Example 1. From the experimental data, it can be seen that compared with Example 1, the quasi-static puncture force is reduced to 1757N, and the number of wear resistance is reduced to 9463 times. The reason for this is that the dosage of MOF material is halved, which reduces the dispersed phase of the impregnation liquid and can react with Ca 2+ The reduction of coordinated carboxyl groups leads to a loose network structure, so the anti-puncture performance is weakened; on the other hand, since the MOF material has the shape of granular powder, it can enhance the wear resistance of the fabric. Therefore, when the amount of MOF material is halved, the wear resistance of the fabric is reduced to 9463 times.
[0082] Comparative Example 2: In step 2: preparation of the impregnation solution, the MOF material was removed, and the rest was the same as in Example 1. From the experimental data, it can be seen that compared with Example 1, the quasi-static puncture force was reduced to 1660N, and the number of wear resistance was reduced to 9433 times. The reason for this is that the MOF material was removed, which reduced the dispersed phase of the impregnation solution and enabled it to be separated from the Ca 2+The number of coordinated carboxyl groups is reduced, resulting in a loose network structure that can be formed, so the anti-puncture performance is weakened; on the other hand, since the MOF material has the shape of granular powder, it can enhance the wear resistance of the fabric. Therefore, when the MOF material is removed, the wear resistance of the fabric is reduced to 9433 times.
[0083] Comparative Example 3: Step 4 is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the quasi-static puncture force has no obvious change, and the number of wear times is reduced to 8450 times. The reason for this is that the wear-resistant coating is removed, resulting in poor wear resistance of the fabric, thereby reducing the number of wear times.
[0084] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0085] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A processing technology for wear-resistant and puncture-resistant gloves, characterized by: The following steps are involved: Step 1: heat-twisting and heat-setting the yarn of ultra-high molecular weight polyethylene fiber to prepare a fabric; Step 2: dilute the impregnation liquid and anhydrous ethanol, then immerse the fabric in the dilution, and obtain the puncture-resistant fabric after drying; wherein the preparation steps of the impregnation liquid are as follows: S1: Mix transition metal nitrate, pyridine-2,6-dicarboxylic acid and deionized water, and stir ultrasonically for 40-60 minutes. Then, hydrothermally react the reactants at 100-120°C for 65-75 hours. After cooling to 20-25°C, vacuum filter, wash and dry to obtain MOF material. S2: dissolving polylactic acid in polyethylene glycol, then adding MOF material to form a mixture, ball-milling the mixture for 10-14 hours to obtain a suspension; adding Ca(NO3)2·4H2O to the suspension, ball-milling again for 10-14 hours to obtain an impregnation solution; in the preparation of the impregnation solution, by weight, 8-10 parts of transition metal nitrate, 8-10 parts of pyridine-2,6-dicarboxylic acid, 24-30 parts of deionized water, 6-12 parts of polylactic acid, 40-50 parts of polyethylene glycol, and 15-25 parts of Ca(NO3)2·4H2O; Step three: Mix epoxy resin, aluminum hydroxide, titanium boride and curing agent, and stir them ultrasonically to obtain a wear-resistant coating; apply the wear-resistant coating on the surface of the puncture-resistant fabric, and obtain the finished product after drying and cutting.
2. The processing technology of the wear-resistant and puncture-resistant gloves according to claim 1, characterized in that: In step 1, heat twisting is to twist the yarn at 70-80°C, and heat setting is to keep the temperature at 55-65°C for 0.5-1.5h.
3. The processing technology of the wear-resistant and puncture-resistant gloves according to claim 1 is characterized in that: In step 2, the impregnation liquid and anhydrous ethanol are diluted in a volume ratio of 1:1 to a mass concentration of 15-25%, the fabric is impregnated for 2-4 minutes, and dried at 60-70°C for 4-6 hours.
4. The processing technology of the wear-resistant and puncture-resistant gloves according to claim 1 is characterized in that: In step three, the components of the wear-resistant coating are used in the following amounts, by mass: 25-35 parts of epoxy resin, 3-5 parts of aluminum hydroxide, 3-5 parts of titanium boride, and 10-20 parts of curing agent.
5. The processing technology of the wear-resistant and puncture-resistant gloves according to claim 4, characterized in that: The curing agent is a cardanol modified amine curing agent.
6. The processing technology of the wear-resistant and puncture-resistant gloves according to claim 1, characterized in that: In step 3, during ultrasonic stirring, the rotation speed is 1500-2000 rpm, the temperature is 40-50° C., and the stirring time is 60-80 min.
7. The processing technology of the wear-resistant and puncture-resistant gloves according to claim 1, characterized in that: In step 3, the coating amount is 30-40g / m 2 , dry at 75-85℃ for 4-6h.
8. A wear-resistant and puncture-resistant glove, characterized in that: Obtained by processing according to the processing technology described in any one of claims 1-7.
Citation Information
Patent Citations
Production process of anti-friction polyester chemical fiber carpet
CN111074546A
Cited By
A kind of composite material that is light, thin, breathable and has high wear resistance
CN122649257A